Is a Child with Intellectual Disabilities Able to Forgive? - Błeszyński, Jacek J. (Paedagogia Christiana, 2016)
This paper discusses the problem of awareness of forgiveness by people with intellectual disability. This article is based on research. The summary presented proposals concerning awareness of understanding and using the concept of forgiveness. We can say that the word itself is based on reflection gained in practice.